2008
DOI: 10.1002/ptr.2708
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone protects dopaminergic neurons against MPP+ and rotenone

Abstract: Thymoquinone is the main active constituent of Nigella sativa seeds with antioxidant and antiinflammatory properties. In the present study, primary dopaminergic cultures from mouse mesencephala were used to investigate the neuroprotective effects of thymoquinone against MPP(+) and rotenone toxicities. MPP(+) (10 microm on day 10 in vitro (i.v.) for 48 h) significantly decreased the number of THir by 40% compared with untreated control cultures. Rotenone at both short (20 nm on day 10 i.v. for 48 h) and long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 30 publications
3
43
0
1
Order By: Relevance
“…Some studies reported that Nigella sativa can be effective in the treatment of neurological diseases such as depression [7] [16]. Also, in one study, the protective effect of thymoquinone, one of the main chemicals in black seed on dopamine-producing cells against MPP+ and rotenone has been confirmed [8]. The results of this study confirmed usefulness of antioxidants existing in black seed; however, this hypothesis needs to be tested clinically.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Some studies reported that Nigella sativa can be effective in the treatment of neurological diseases such as depression [7] [16]. Also, in one study, the protective effect of thymoquinone, one of the main chemicals in black seed on dopamine-producing cells against MPP+ and rotenone has been confirmed [8]. The results of this study confirmed usefulness of antioxidants existing in black seed; however, this hypothesis needs to be tested clinically.…”
Section: Discussionsupporting
confidence: 66%
“…Muscular rigidity (usually named catatonia) was determined using the method of Morpurgo (8). The development of muscle rigidity was observed and scored as follows: Stage 1, mice move freely when placed on the table, score allocated = 0; Stage, mice move only when touched or pushed, score allocated = 0.5; Stage 3, mice placed on the table with one of the front paws alternately on a 1cm high block.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although various studies have been performed on antioxidant activity of black cumin extracts (Ilhan, Gurel, Armutcu, Kamisli, & Iraz, 2005;Mariod, Ibrahim, Ismail, & Ismail, 2009), we have not encountered any report evaluating cholinesterase and tyrosinase inhibitory of the black cumin. On the other hand, thymoquinone, a main constituent in NS, was found to protect primary dopaminergic neurons against MPP(+) and rotenone relevant to Parkinson's disease (Radad, Moldzio, Taha, & Rausch, 2009) and, thus, TYRO inhibitory activity of the seed extract of NS could be searched since thymoquinone might be inhibiting this enzyme and being responsible for inhibitory effect of this extract. Previous papers on fatty acid composition of the black cumin oil, in which linoleic acid was established as the main fatty acid, were in accordance with our findings (Kokdil & Yilmaz, 2005;Nergiz & Otles, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies attribute significant neuroprotective effects to flavonoid compounds, and this has been frequently associated with the antioxidant properties of these substances, [22][23][24] which could explain the observed cytoprotection effects of FR3 in our animal model of neurodegeneration. Thus, we propose that such an effect is related to the high contents of flavonoids present in the leaves.…”
Section: Neuroprotective Propertiesmentioning
confidence: 81%